ANALISIS PELAKSANAAN PEMBELAJARAN ONLINE DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA (STUDI KASUS PADA PROGRAM KEAHLIAN AKUNTANSI DI SMK MULTI MEKANIK MASMUR PEKANBARU) - Annisa Husnul Khatimah; Gimin Gimin; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine (1) how the implementation of online learning in the Accounting Skills Program at SMK Multi Mekanik Masmur Pekanbaru, (2) how student learning outcomes after implementing online learning at the Accounting Skills Program at SMK Multi Mekanik Masmur Pekanbaru, (3) is there an effect of the implementation of online learning on student learning outcomes of the Accounting Skills Program at SMK Multi Mekanik Masmur Pekanbaru. This research method uses descriptive quantitative research with this type of research is a case study. The population in this study were students of class X in the Accounting Skills Program of SMK Multi Mekanik Masmur Pekanbaru by taking a sample of the entire population as many as 22 students. Collecting data using questionnaires and documentation, data analysis using descriptive analysis and regression analysis. The results of the study stated that: (1) the implementation of online learning for class X students of the Accountant Expertise Program at SMK Multi Mekanik Masmur Pekanbaru in the subjects of Basic Accounting and Business Economics was in the good category, namely 45.4%. (2) the results of studying Basic Accounting and Business Economics of class X students of the Accounting Expertise Program at SMK Multi Mekanik Masmur Pekanbaru after carrying out online learning in a good category, namely 63.64% for Basic Accounting subjects and 90.91% for Business Economics subjects. (3) simultaneous online learning has no effect on the learning outcomes of basic accounting and business economics for class X students of the Accounting Skills Program at SMK Multi Mekanik Masmur Pekanbaru. Where Basic Accounting learning outcomes are influenced by online learning by 2.7%, while Business Economics learning outcomes are influenced by online learning by 2.7%.Key Words: Online Learning, Learning Outcomes